What is Driving Income Inequality? Differences between Japan and the United States - Kurihara, Yutaka; Fukushima, Akio (Archives of Business Research, 2025)
It is said that income inequality in Japan has increased. In fact, the Gini coefficient reflects this situation, although not as much as in the United States. The ultra-low, zero, or negative interest rate policy that has been implemented for more than 30 years to avoid deflation has been cited as the reason for the increase in income inequality. The prevailing view is that low interest rates have led to an increase in stock and real estate prices, driving a gap between high-income earners and low-income earners. It has also been suggested that the depreciation of the yen caused by low interest rates has led to an increase in exports from exporting firms, many of which are large firms in Japan, and has exacerbated the inequality. This study examines the causes of income inequality using empirical methods. The estimation results indicate that low interest rates and soaring asset prices are not the cause of income inequality. On the other hand, it is confirmed that the increase in university enrollment has led to income inequality. In order to correct this inequality, it is necessary to combine fiscal policy appropriately with monetary policy, rather than relying too much on monetary policy.